Avascular necrosis of bone complicating corticosteroid replacement therapy. Issue 3 (June 1983) - Williams, P L; Corbett, M
Abstract : Two patients who developed widespread severe avascular necrosis of bone while on steroid replacement therapy are described. One, a diabetic, underwent yttrium-90 pituitary ablation for retinopathy and developed avascular necrosis within 18 months of starting prednisolone. The other, who had Addison's disease, developed avascular necrosis within 14 months of starting cortisol replacement therapy. Both cases came to bilateral total hip replacement.